Bone Health in Rats With Temporal Lobe Epilepsy in the Absence of Anti-Epileptic Drugs - Brady, Rhys D.; Wong, Ker Rui; Robinson, Dale L.; Mychasiuk, Richelle; McDonald, Stuart J.; D’Cunha, Ryan A.; Yamakawa, Glenn R.; Sun, Mujun; Wark, John D.; Lee, Peter Vee Sin; O’Brien, Terence J.; Casillas-Espinosa, Pablo M.; et al. (Frontiers in Pharmacology, 2019)
Rationale: Epilepsy patients often exhibit reduced bone mineral density and are at an increased risk of bone fracture. Whether these bone abnormalities are due to the use of anti-epileptic drugs (AED’s) or the disease itself is unknown. For example, although decreased bone health in epilepsy patients is generally attributed to the use of AED’s, seizures can also trigger a number of physiological processes that have the potential to affect bone. Therefore, to assess whether bone abnormalities occur in epilepsy in the absence of AED’s, the current study investigated mechanical characteristics and trabecular bone morphology in rats with chronic temporal lobe epilepsy. Methods: Ten-week old male Wistar rats underwent kainic acid-induced status epilepticus (SE; n = 7) or a sham procedure (n = 9). Rats were implanted with EEG recording electrodes at nine weeks post-SE, and video-EEG was continuously recorded for one week at 10- and 22-weeks post-SE to confirm that SE rats had spontaneous seizures. Open-field testing to assess locomotion was conducted at 23-weeks post-SE. At 24-weeks post-SE, rats were euthanized and tibia were extracted to determine trabecular morphology by micro-computed tomography (µCT), while femurs were used to investigate mechanical properties via 3-point bending. Results: All post-SE rats had spontaneous seizures at 10- and 22-weeks post-SE, while none of the sham rats had seizures. µCT trabecular analysis of tibia revealed no differences in total volume, bone volume, bone volume fraction, trabecular number, or trabecular separation between post-SE or sham rats, although post-SE rats did have increased trabecular thickness. There were also no group differences in total distance travelled in the open field suggesting that activity levels did not account for the increased trabecular thickness. In addition, no differences in mechanical properties of femurs were observed between the two groups. Conclusion: There was a lack of overt bone abnormalities in rats with chronic temporal lobe epilepsy in the absence of AED treatment. Although further studies are still needed, these findings may have important implications towards understanding the source (e.g., AED treatments) of bone abnormalities in epilepsy patients.